Revealing the location and dynamics of a concealed binding site in the dopamine transporter - Rong Zhu; Walter Sandtner; Thomas Stockner; Alexander Heilinger; Marion Holy; Oliver Kudlacek; Linda Wildling; Kusumika Saha; Anna Sophie Fröhlich; Michael Bindl; Paraskevi Tziortzouda; Anna Haider; et al. (Nature Communications)
Abstract The dopamine transporter (DAT) is linked to neuropsychiatric disorders including ADHD, Parkinson’s disease, and substance use disorders. Accordingly, DAT is the target of illicit drugs and clinically important medicines. However, the number and function of ligand binding sites in DAT is enigmatic due to conflicting data from available structures and molecular pharmacology. Herein, we design force sensors with DAT ligands and measure their interaction forces with wild-type and mutated DATs, from which two distinct populations of unbinding strengths and off-rates are detected. The high-force population is reduced by V152I and S422A mutations, or by substituting Na+ with K+ or NMDG+. In contrast, several modifications including mutation G386H, acetylation of K92 and K384, mutation K92A, mutation K384A, or protonation of H477 decrease the low-force population. The present data delineate the threshold of binding strength, which may account for certain ligand binding sites to be imperceptible in crystal or cryo-EM structures. Furthermore, the force spectra provide the information on the position and kinetic rates of a herein detected ligand binding site in DAT.